2021
DOI: 10.1111/jcmm.16313
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides extracted from balanophora polyandra Griff (BPP) ameliorate renal Fibrosis and EMT via inhibiting the Hedgehog pathway

Abstract: Renal interstitial fibrosis (RIF) is a crucial pathological change leading to chronic kidney disease (CKD). Currently, no effective medicines have been available for treating it. In our research, we examined the effects of polysaccharides extracted from Balanophora polyandra Griff (BPPs) on kidney fibrosis and epithelial to mesenchymal transition (EMT) in vivo and in vitro, aiming to explore the underlying mechanisms. By using the mice with unilateral urethral obstruction (UUO) as experimental subjects, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…35 TGF-β is the most prominent inducer of EMT, and several researchers reported the stimulation of the EMT program and the appearance of myofibroblast markers in the UUO-induced kidneys. 34,36 In line with these studies, our results revealed low renal E-cadherin levels and a substantial increase in the expression of vimentin and α-SMA in the kidneys of the UUO group, implying the dysregulated cellular adhesion of tubular epithelial and myofibroblast activation. Moreover, our in vitro data also confirmed the activation of the EMT program in renal tubular epithelial NRK 52E cells upon TGF-β induction.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…35 TGF-β is the most prominent inducer of EMT, and several researchers reported the stimulation of the EMT program and the appearance of myofibroblast markers in the UUO-induced kidneys. 34,36 In line with these studies, our results revealed low renal E-cadherin levels and a substantial increase in the expression of vimentin and α-SMA in the kidneys of the UUO group, implying the dysregulated cellular adhesion of tubular epithelial and myofibroblast activation. Moreover, our in vitro data also confirmed the activation of the EMT program in renal tubular epithelial NRK 52E cells upon TGF-β induction.…”
Section: Discussionsupporting
confidence: 87%
“…Simultaneously, the tubular epithelial cells deficient in adhesion markers attain myofibroblast features distinguished by the production of α-SMA, vimentin, and fibronectin. 34 In particular, myofibroblasts are considered the primary source of ECM in interstitial space and are involved in aggravating the fibrogenic transformation of the kidneys. 35 TGF-β is the most prominent inducer of EMT, and several researchers reported the stimulation of the EMT program and the appearance of myofibroblast markers in the UUO-induced kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Renal tubular epithelial phenotypic transformation (EMT) is characterized by the transformation of the epithelial phenotype into a fibroblast-like mesenchymal phenotype, in which E-cadherin expression is reduced, and N-cadherin expression is increased. Epithelial cells lose top base polarity and, on the other hand, intercellular adhesion and gain mesenchymal properties ( Liu et al, 2020 ; Li L. et al, 2021 ). This change is critical, not just in renal fibrosis, but in various biological processes such as cancer progression, organization palingenesis, embryo growth, and wound coalescence.…”
Section: Pathological Mechanisms Of Rifmentioning
confidence: 99%
“…Studies have shown that BPP administration inhibited the hedgehog signaling pathway. Therefore, BPPs can suppress the EMT process by attenuating the activity of the hedgehog signal conduction, thereby improving RIF ( Briscoe, 2009 ; Jenkins, 2009 ; Ding et al, 2012 ; Rauhauser et al, 2015 ; Li L. et al, 2021 ). Sedum is extracted from rhodiola rosea and widely used in the clinic.…”
Section: Mechanisms Of Rif Interventionmentioning
confidence: 99%
“…The activation of hedgehog signaling has been shown to be associated with EMT in liver cancer cells ( Ding et al, 2017 ). In the UUO model, inhibition of hedgehog signaling pathway was also demonstrated to improve EMT in HK-2 cells ( Li et al, 2021c ). In the DN model, Zhao et al found that hyperglycemia stimulated the expression of the Hhip by enhancing the generation of ROS, and TGF-β1/Smad2 pathway was also activated, which promoted the transition of glomerular endothelial cells to the mesenchyme.…”
Section: Epithelial-to-mesenchymal Transition and Endothelial-to-mese...mentioning
confidence: 99%